College institutional characteristics and the use of barrier methods among undergraduate students. Issue 6 (2nd November 2017) - Griner, Stacey B.; Thompson, Erika L.; Vamos, Cheryl A.; Logan, Rachel; Vázquez-Otero, Coralia; Daley, Ellen M.
Abstract: Sexually transmitted infections (STIs) may be prevented through the use of barrier methods, but rates of use among US college students are low. Previous research focuses on individual-level factors influencing barrier method use, but few studies consider community-level influences. This study examined consistency of barrier use by college institutional characteristics including region, enrolment, control (public or private), locale, type, or religious-affiliation. Data from the Autumn 2013 US National College Health Assessment-II ( n = 13, 400; 57 colleges) were analysed. Prevalence ratios were calculated for consistent barrier method use during vaginal, oral and anal sex. Consistent barrier use during vaginal sex was associated with enrolment at a college in the Northeast, compared to the West (aPR: 1.16 [95%CI 1.01–1.29], p = 0.04), and enrolment at larger institutions compared to smaller colleges. Attending a private college or university was associated with more consistent barrier method use during vaginal sex and anal sex compared to those attending a public college or university. Findings demonstrate differences in barrier method use by institutional-level factors, and future research should consider the role of the college community. US college-based health promotion should include barrier method interventions at multiple levels if STIs are to be reduced.